2022
DOI: 10.1136/oemed-2022-108371
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide use in farming and other jobs in relation to non-Hodgkin’s lymphoma (NHL) risk

Abstract: ObjectivesGiven mixed evidence for carcinogenicity of current-use herbicides, we studied the relationship between occupational herbicide use and risk of non-Hodgkin’s lymphoma (NHL) in a large, pooled study.MethodsWe pooled data from 10 case-control studies participating in the International Lymphoma Epidemiology Consortium, including 9229 cases and 9626 controls from North America, the European Union and Australia. Herbicide use was coded from self-report or by expert assessment in the individual studies, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Residential use of this chemical has been identified as having a null association with NHL in previous analyses by itself in this dataset 41 and in a mixture in a pooled analysis of several cohorts. 42 The former result supports a previous Bayesian analysis of these data that estimated global mixture effects and cumulative unmeasured spatial risk simultaneously 43 as well as one using WQS regression that found large importance weights for these and two other pesticides (γ-chlordane and o-phenylphenol) for a positive and significant mixture effect in Iowa. 10 The latter result was also identified in the Bayesian analysis, 43 and in another analysis a WQS index constrained to have positive association with NHL risk estimated a very small importance weight for 2,4-D, which is consistent with having a large weight in a mixture showing an inverse association with NHL.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Residential use of this chemical has been identified as having a null association with NHL in previous analyses by itself in this dataset 41 and in a mixture in a pooled analysis of several cohorts. 42 The former result supports a previous Bayesian analysis of these data that estimated global mixture effects and cumulative unmeasured spatial risk simultaneously 43 as well as one using WQS regression that found large importance weights for these and two other pesticides (γ-chlordane and o-phenylphenol) for a positive and significant mixture effect in Iowa. 10 The latter result was also identified in the Bayesian analysis, 43 and in another analysis a WQS index constrained to have positive association with NHL risk estimated a very small importance weight for 2,4-D, which is consistent with having a large weight in a mixture showing an inverse association with NHL.…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, we found a negative and significant spatially varying association for another mixture of pesticides and NHL in northern and western Iowa, with 2,4‐D being the most important chemical in this mixture. Residential use of this chemical has been identified as having a null association with NHL in previous analyses by itself in this dataset 41 and in a mixture in a pooled analysis of several cohorts 42 . The former result supports a previous Bayesian analysis of these data that estimated global mixture effects and cumulative unmeasured spatial risk simultaneously 43 as well as one using WQS regression that found large importance weights for these and two other pesticides (normalγ$$ \upgamma $$‐chlordane and o ‐phenylphenol) for a positive and significant mixture effect in Iowa 10 .…”
Section: Discussionmentioning
confidence: 63%
“…Hira Saleem, 1 Abdul Rafeh Awan 2 Madam, Glyphosate, commercially known as Round Up, is one of the most widely used herbicides and pesticides worldwide. As a synthetic organophosphate compound, it comes in a crystalline, odourless and colourless form.…”
Section: Glyphosate -A Silent Slow Killer?mentioning
confidence: 99%
“…As of right now, there is a multitude of studies that link glyphosate to several morbidities. When a combined 9229 cases of farmers from North America, the European Union and Australia were assessed, glyphosate was directly linked to an increase in the onset of follicular lymphoma 2 . It was also associated with allergic and non-allergic wheezing among farm women in the Agricultural Health Study (2005-2010), which focused on farmers in Iowa and North Carolina 3 .…”
Section: Glyphosate -A Silent Slow Killer?mentioning
confidence: 99%
“…The early reviews showed that farmers have a lower risk of most major causes of death than the general population particularly in terms of total mortality, total cancer, health diseases and speci c cancers like lung cancer [5][6][7]. However, according to cohort and case-control studies [8,9], this occupational group has a higher risk for certain types of cancers, particularly Soft Tissue Sarcomas (STSs), non-Hodgkin lymphomas (NHLs) [10][11][12][13], Hodgkin's disease (HD), leukemia, multiple myeloma (MM) [14], prostate cancer [15][16][17][18] and cancer of the skin and lip [5,6].…”
Section: Introductionmentioning
confidence: 99%